Adapting to a Cookie-less Future: Technical Strategies for Digital Advertising - Madhusudhanarao Chebrolu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The digital advertising landscape is experiencing a transformative shift as the industry moves away from third-party cookies toward privacy-preserving technologies. This comprehensive article explores the challenges and opportunities presented by this transition, examining emerging technical solutions including browser extensions, contextual advertising systems, and server-side tracking architectures. The article explores the implementation of advanced data strategies, AI-driven predictive models, and privacy sandbox technologies while highlighting the critical balance between maintaining advertising effectiveness and ensuring user privacy. Through analysis of current industry practices and technological innovations, this article provides insights into how organizations can successfully navigate the cookie-less future while building more sustainable and trusted relationships with their audiences.